Cold surge invading the Beijing 2022 Winter Olympic Competition Zones and the predictability in BCC‐AGCM model - Xiang Li; Hui Gao; Ting Ding (Atmospheric Science Letters, 2021)
Abstract The 24th Olympic and Paralympic Winter Games will be held at three competition zones in North China. The cold surge is considered as the most dominant weather affecting the game schedule by the Organizing Committee of Beijing Olympic Games. In this article, both the frequency of 124 cold surge cases invading the competition zones and the corresponding atmospheric circulation during the winters of 1985–2020 are first analyzed. The results show that the frequency has not been reduced by the global warming. On the contrary, it has been increasing slightly in recent decade. By verifying the forecast skill of temperature drop at the zones in Beijing Climate Center‐Atmospheric General Circulation Model (version 2.2), it is found that the average efficient forecast leading time with persistent temperature drop exceeding 1°C is about 7 days, but significant differences exist among the individual cases. The 20 best forecasts and the 20 worst forecasts were selected for further analysis. In the 20 worst forecasts, the cold surge processes cannot be forecasted even 1 day in advance. It is mainly due to the great deviation of the simulated circulation from the observation, especially the failure to forecast the enhancement of the Siberian High especially in its southeast part before the cold surge occurrence. While in the 20 best forecasts, the model can capture the cold surges 9 days before the occurrence, owing to its skill in forecasting the positive sea level pressure anomalies from the southern Barents Sea and the Kara Sea to eastern China. Above evaluations can provide useful information to the forecast of cold surge invading the competition zones beyond 1 week.